China’s accession to the WTO and its impact on global agricultural trade - Glauber, Joseph W. (Cambridge University Press, 2023)
China’s rapid rise as a leading global exporter of manufacturing goods since its accession to the WTO in 2001 has been the focus of both admiration and, increasingly, concern (Mavroidis and Sapir, 2021). But it is sometimes overlooked that China is also a large importer of goods, particularly agricultural products. Since China’s accession to the WTO, China’s agricultural exports have increased by 8 per cent annually while imports have risen by almost twice that rate. China has become the world’s largest importer of agricultural products and the first or second largest destination for many of the world’s top agricultural exporters such as the US, Brazil, Australia, New Zealand, Canada, and Argentina.